Ischemic stroke related to systemic sarcoidosis: Report of complete autopsy examination - Wei Wang; Rongying Li; Xavier Rivera Rivera; Noah Reilly; Meenakshi Bhattacharjee; Bihong Zhao, MD, PhD (Elsevier, 2021)
Sarcoidosis is a systemic idiopathic granulomatous disease that most commonly presents with lungs and hilar lymph node involvement. Clinical manifestation with acute ischemic stroke, with central neurological and cardiac involvement is extremely rare. Herein we report the case of a 60-year-old African American woman with history of chronic heart failure and pacemaker implantation, who presented with acute ischemic stroke, and died within 34 h of hospitalization. On autopsy, well-formed non-caseating granulomas were present in the myocardium, adventitia of the left main coronary artery, all lobes of bilateral lungs, pleura, liver, and spleen. The brain also showed granulomas, with predominantly leptomeningeal and focal parenchymal involvement of the central basal brain tissue (hypothalamic region), but without vascular wall involvement. Granulomas were also present within the thyroid as well as an incidental finding of a Hürthle-cell adenoma (HCA). We believe that left internal carotid artery and left middle cerebral artery obstruction, possibly thromoboembolic from the heart, was the cause of acute regional brain ischemia. This rare case illustrates the importance of the autopsy in the diagnosis of unexpected medical conditions; and also that sarcoidosis may play an etiologic role in acute ischemic stroke.